How to get multi-agent systems accepted in industry?. (20th May 2009) - Weyns, Danny; Helleboogh, Alexander; Holvoet, Tom
With many researchers in the Multi-Agent System (MAS) community, we share the opinion that too much of the quality and relevant research in the area of MAS is underrepresented in the development of complex distributed systems in practice today. In our experience, a Babylonic mismatch is a crucial factor in this fact – research on MAS profiles itself as an isolated community and, as such, may create artificial thresholds to convince mainstream software developers of its merits. We argue that integrating the concepts and techniques from agent-based software engineering within mainstream software engineering provides opportunities to amplify the industrial adoption of MAS. To ground this position, we discuss MAS engineering from the perspective of the software engineering area that we are most familiar with: software architecture.